2017
DOI: 10.1021/jacs.7b00612
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Evidence of Emergent Equilibrium Isotope Effects in Anion Receptor Complexes

Abstract: The measurement of a deuterium equilibrium isotope effect (EIE) for the aryl CH···Cl– interaction of anion receptor 1H/1D is reported. Computations corroborate the results of solution measurements for a small, normal EIE in the full complex (KaH/KaD = 1.019 ± 0.010). Interestingly, isotope effects involving fragments of the anion receptor (urea, aryl ring, etc.) are predicted to produce an inverse effect. This points to an unusual and subtle structural organization effect of the anion receptor complex that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…13), and thus we embarked on a study with collaborator Paul Cheong's lab to investigate EIEs in an aryl CH HB an anion receptor. 51 In this investigation, receptors 21a H and 21a D were titrated with chloride in d 6 -DMSO and monitored through 13 C NMR titrations. We reported a normal DEIE, with K a 21 aH / K a 21 aD = 1.019 +/ − 0.010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13), and thus we embarked on a study with collaborator Paul Cheong's lab to investigate EIEs in an aryl CH HB an anion receptor. 51 In this investigation, receptors 21a H and 21a D were titrated with chloride in d 6 -DMSO and monitored through 13 C NMR titrations. We reported a normal DEIE, with K a 21 aH / K a 21 aD = 1.019 +/ − 0.010.…”
mentioning
confidence: 99%
“…We reported a normal DEIE, with K a 21 aH / K a 21 aD = 1.019 +/ − 0.010. 51 We also reported the computed DEIEs of fragments of the receptors (Fig. 13).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] This halogen bonding interaction has attracted interest in many elds, such as molecular biology 6,7 and crystal engineering, 8,9 due to its high molecular selectivity and linear directionality. [10][11][12][13][14] In particular, halogen bonding has been positively applied to develop new functional materials [15][16][17][18] since Nguyen et al rst synthesized liquid crystals designed with halogen bonds in 2004. 19 An example is the Rotaxane structure with iodo groups synthesized by Barendt et al that selectively recognized nitrogen anions via halogen bonding, producing drastic color changes.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this aim, our lab has developed several arylethynyl frameworks (Figure 1) capable of binding a variety of anionic guest molecules, including halides, [14][15][16][17][18] oxoanions, [19][20][21] and hydrochalcogenides. [22][23][24] These hosts take advantage of both their multidentate binding pockets formed from the meta-substitution of the phenyl or pyridyl cores with two arylethynyl arms as well as the fluorescent nature of the -conjugated backbone.…”
Section: Introductionmentioning
confidence: 99%
“…14 This opened a floodgate of 13 eventual co-advised students and postdocs over the next 14 years who explored anion--interactions, the effect of increasing or reducing the number of urea binding units, the effects of different heterocyclic cores, and the physical organic chemistry of these receptors and their guests. 16,[19][20][21][22][23][24] Along the way, graduate student Blake Tresca further improved upon the early designs by replacing the pH-sensitive pyridine core with a benzene as in 2 and showed that the C-H•••anion interaction could be tuned by installing electron-donating/electron-withdrawing groups para to the CH unit. 26 the National Academy of Inventors.…”
Section: Introductionmentioning
confidence: 99%